2005
DOI: 10.1097/00042728-200506000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Ointment versus Petrolatum for Management of Auricular Wounds

Abstract: BACKGROUND. Surgeons frequently create defects on the ear in the treatment of cutaneous malignancies. Potentially significant complications of second-intention healing on the ear are suppurative and inflammatory chondritis. Consequently, many physicians advocate the use of oral or topical prophylactic antibiotics after auricular surgery.OBJECTIVE. The purpose of this study is to compare the efficacy of gentamicin ointment with that of petrolatum for the prevention of suppurative chondritis during second-intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…), constituted the other major group of products (Table 1). In addition, products from various manufacturers elicited positive reactions, and their ingredients are shown in Table 1 (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Skin Testing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), constituted the other major group of products (Table 1). In addition, products from various manufacturers elicited positive reactions, and their ingredients are shown in Table 1 (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Skin Testing Resultsmentioning
confidence: 99%
“…Product testing was performed either as a use test or a patch test. In most patients (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), the use test was employed, as the product being tested is normally either applied and then occluded under adhesive dressings or is the adhesive dressing itself. For the use test, we identified an area of uninvolved skin of ∼10 cm 2 on which to apply the product.…”
Section: Methodsmentioning
confidence: 99%
“…8 Two more recent studies found slightly lower rates of complication, with 5.6% to 8.33% of patients experiencing inflammatory chondritis and 0% to 5.56% of patients experiencing suppurative chondritis. 2,7 These higher rates of complication in auricular surgery have been attributed to extensive manipulation of the auricular cartilage 2,7 and colonization of moist tissue with higher bacterial counts. 8 P. aeruginosa is a particular concern because it has been implicated in infections after surgical manipulation, ear piercing, and acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…It also supports findings of a previous study, which showed that second-intention healing for auricular wounds has a low incidence of infection. 7 Reconstructed auricular wounds have demonstrated a higher incidence of infection and may warrant prophylactic antibiotics. 8 A 1-week course of 500 mg of levofloxacin daily is estimated to cost $70.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation